2000
DOI: 10.1083/jcb.151.4.879
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 9 and Vascular Endothelial Growth Factor Are Essential for Osteoclast Recruitment into Developing Long Bones

Abstract: Bone development requires the recruitment of osteoclast precursors from surrounding mesenchyme, thereby allowing the key events of bone growth such as marrow cavity formation, capillary invasion, and matrix remodeling. We demonstrate that mice deficient in gelatinase B/matrix metalloproteinase (MMP)-9 exhibit a delay in osteoclast recruitment. Histological analysis and specialized invasion and bone resorption models show that MMP-9 is specifically required for the invasion of osteoclasts and endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
418
1
13

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 533 publications
(445 citation statements)
references
References 67 publications
13
418
1
13
Order By: Relevance
“…VEGF has been found, by others, to be important in the process of calcification and is expressed by hypertrophic chondrocytes (Gerber et al, 1999;Engsig et al, 2000;Haigh et al, 2000;Karsenty, 2001). The invasion of blood vessels associated with bone formation is controlled to some extent by VEGF produced by the hypertrophic chondrocytes (Gerber et al, 1999;Furumatsu et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…VEGF has been found, by others, to be important in the process of calcification and is expressed by hypertrophic chondrocytes (Gerber et al, 1999;Engsig et al, 2000;Haigh et al, 2000;Karsenty, 2001). The invasion of blood vessels associated with bone formation is controlled to some extent by VEGF produced by the hypertrophic chondrocytes (Gerber et al, 1999;Furumatsu et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Osteoclasts degrade bone by the polarized secretion of proteolytic enzymes (e.g., cathepsin K) and acids, which hydrolyze and solubilize the organic and inorganic components of bone, respectively (Boyce 2013). MMP-9 released from the ruffled border is highly expressed at early stages of osteoclast development and in mature osteoclasts, and helps regulate the osteoclast migration required for bone resorption (Engsig et al 2000;Reponen et al 1994). It is reported that OPG blocks the later stages of osteoclast differentiation in mice and suppresses the activation of mature osteoclasts (Simonet et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This is confirmed by studies that show a delay in the recruitment of osteoclasts and endothelial cells at the early stages of endochondral ossification in MMP9 −/− mice. Moreover, this recruitment is under the influence of a major angiogenic factor, VEGF [42]. VEGF is made by the terminal hypertrophic chondrocytes under the control of Runx-2 [43] and is linked to the expression of another angiogenic factor, connective tissue growth factor (CTGF) [44].…”
Section: Mmp9 Is a Key Regulator Of Early Growth Plate Angiogenesis Amentioning
confidence: 99%
“…MMP9 is expressed in osteoclasts, endothelial cells and other cell types, including bone marrow stromal cells, whereas MMP13 is expressed in the hypertrophic chondrocytes and osteoblasts. MMP9 is specifically required for the invasion of osteoclasts and endothelial cells into the discontinuously mineralized hypertrophic cartilage that fills the core of the diaphysis and is partially required for the passage of cells through unmineralized type I collagen of the nascent bone collar [42]. Early in postnatal development, MMP13 −/− mice display a small increase in hypertrophic cartilage and trabecular bone (D. Stickens, Z. Werb; unpublished).…”
mentioning
confidence: 99%